Nonlinear dynamic analysis and vibration of eccentrically stiffened S-FGM elliptical cylindrical shells surrounded on elastic foundations in thermal environments. (August 2017) - Dinh Duc, Nguyen; Dinh Nguyen, Pham; Dinh Khoa, Nguyen
Abstract: Elliptical cylindrical shell is one of shells with special shape. Up to date, there is no publication on vibration and dynamic of functionally graded elliptical cylindrical shells. Therefore, the purpose of the present study is to investigate the nonlinear dynamic response and vibration of imperfect eccentrically stiffness functionally graded elliptical cylindrical shells on elastic foundations using both the classical shell theory (CST) and Airy stress functions method with motion equations using Volmir's assumption. The material properties are assumed to be temperature - dependent and graded in the thickness direction according to a Sigmoid power law distribution (S-FGM). The S-FGM elliptical cylindrical shell with metal-ceramic-metal layers are reinforced by outside metal stiffeners. Both the S-FGM elliptical shell and metal stiffeners are assumed to be in thermal environment and both of them are deformed under temperature simultaneously. Two cases of thermal loading (uniform temperature rise and temperature variation through thickness) are considered. The nonlinear motion equations are solved by Galerkin method and Runge-Kutta method (nonlinear dynamic response, natural frequencies). The effects of geometrical parameters, material properties, elastic foundations Winkler and Pasternak, the nonlinear dynamic analysis and nonlinear vibration of the elliptical cylindrical shells are studied. The some obtained results are validated by comparing with those in the literature. Highlights: The nonlinear dynamic response and vibration of the eccentrically stiffened S-FGM elliptical cylindrical shells. The S-FGM elliptical shells are reinforced by eccentrically stiffeners and resting on elastic foundations. The S-FGM elliptical shells are in thermal environment with temperature – dependent material properties. The S-FGM elliptical shells and stiffeners are deformed under temperature simultaneously. Two cases of thermal loading - uniform temperature rise and temperature variation through thickness - are considered.